What Can Pinky Hear? - Cousins, Lucy (Walker Books Ltd, 2002)
Pinky is a big-eared bespectacled rabbit discovering the sounds and sights of the world around him.
Keywords: Concepts; Hearing; Juvenile Nonfiction; Sense & Sensation; Rabbits